WRITING PROBLEMS IN JUNIOR HIGH SCHOOL ( SMPN 1) PEMATANGSIANTAR - VITA TESSALONICA REBECCA SIMAMORA; RIBKA G. RITONGA; EGA FITRIA ANGGRAINI; EVA AUDRYNA NAINGGOLAN; SELVIANA NAPITUPULU (CV KULTURA DIGITAL MEDIA, 2022)
This study aims to answer the research problem about the non-linguistic problems in writing faced by grade eight at Junior High School 1 Pematangsiantar. The objective of this study was to identify some non-linguistic problems in writing faced by the grade eight at Junior High School 1 Pematangsiantar. Furthermore, the data were analyzed by using descriptive quantitative. The research participants of this study were thirty two students from grade eight of Junior High School 1 Pematangsiantar who had writing scores were the passing grade criteria. In addition, the instruments employed closed-ended questionnaire and semi-structured interview. The result of the study revealed that the grade eight encountered several non-linguistic problems in writing, comprised of: (1)students lacked of learning motivation, (2) lacked of support from people surrounding, poor facilities, and teacher’s related issues. Moreover, not all the students encountered those problems because every student had different linguistic problems in writing. Therefore, some contributions from the headmaster, English teacher and the students are needed in order to minimize those kinds of linguistic problems.